2008
DOI: 10.1038/aja.2008.17
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific PSA reference ranges in Chinese men without prostate cancer

Abstract: This study is to determine age-specific prostate-specific antigen (PSA) distributions in Chinese men without prostate cancer (PC) and to recommend reference ranges for this population after comparison with other studies. From September 2003 to December 2006, 9 374 adult men aged from 18 to 96 years agreed to participate in the study. After all cases of PC were excluded, 8 422 adult men participated in statistical analysis and were divided into five age groups. Simple descriptive statistical analyses were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 15 publications
4
49
1
Order By: Relevance
“…Using the 95 th percentile total serum PSA values in ng/ml as our upper limit of the reference range and the lowest as 0 ng/ml in this study, the age-specific ranges for our cohort were 0-4.93, 0-6.93, 0-7.80 and 0-9.65 for the age groups 40-49, 50-59, 60-69 and 70-78 respectively which were higher than the values first reported by Oesterling among US white males in I993 including similar studies from Europe and Asia as shown in Table 2 with emphasis on the same 10-year age groups 40-49, 50-59, 60 -69 and 70-79. 13,14,16 Though our age-specific range for the 30-39year group was lower than the comparative European study, this could be because of the limited number (n=6 on Table 1) of men in that group. 13 These various studies had all used same 95 th percentile total PSA values to derive their respective age-specific reference ranges as in this study.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…Using the 95 th percentile total serum PSA values in ng/ml as our upper limit of the reference range and the lowest as 0 ng/ml in this study, the age-specific ranges for our cohort were 0-4.93, 0-6.93, 0-7.80 and 0-9.65 for the age groups 40-49, 50-59, 60-69 and 70-78 respectively which were higher than the values first reported by Oesterling among US white males in I993 including similar studies from Europe and Asia as shown in Table 2 with emphasis on the same 10-year age groups 40-49, 50-59, 60 -69 and 70-79. 13,14,16 Though our age-specific range for the 30-39year group was lower than the comparative European study, this could be because of the limited number (n=6 on Table 1) of men in that group. 13 These various studies had all used same 95 th percentile total PSA values to derive their respective age-specific reference ranges as in this study.…”
Section: Discussionmentioning
confidence: 46%
“…4,17 We noted same race similarity of the 95th percentile total PSA levels (4.93 versus 4.7.8), (6.93 versus 5.47) and (7.80 versus 8.93) for age groups 40-49, 50-59 and 60-69 between this study and that of the recent communitybased study in Nigeria but significant variation with other race groups as shown in Table 3. 11,13,14,16 The little insignificant variation observed between our study and the recent Nigeria study could be due to serum PSA assay methodological differences. This similarity gives credence to the influence of race on PSA values, with men of the same race having similar values while variation existing between race groups.…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…Serum PSA was found to be elevated with age and was clearly shown in various studies conducted among Asian populations such as Chinese, south India, Koreans, Singaporeans, and Japanese [4,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Dubey concluded that in India there is no scientific rationale to advocate routine use of PSA for early detection of PC in Indian males due to low incidence of PC. But the importance to establish reference range of serum PSA for healthy south Indian males to interpret PSA result in benign as well as malignant disorders of prostate was given by Malati and Kumari [4].…”
Section: Discussionmentioning
confidence: 99%